Advances in Chemical Physics, Liquid Polymorphism. - Stanley, H. E. (Advances in chemical physics., 2013)
Advances in Chemical Physics is the only series of volumes available that explores the cutting edge of research in chemical physics. This new guest-edited volume focuses on liquid polymorphism, containing a representative cross-section of research that questions established thinking by scrutinizing the evidence for and against, and inquiring into the possibility and consequences of the existence of more than one liquid phase in a pure substance. Highlighting the quest to understand liquid and vitreous polymorphism, the book features chapters on experiments, theory, and computation.